2016
DOI: 10.1186/s12887-016-0682-y
|View full text |Cite
|
Sign up to set email alerts
|

Under-five mortality pattern and associated risk factors: a case-control study at the Princess Marie Louise Children’s Hospital in Accra, Ghana

Abstract: BackgroundMillions of children under the age of 5 years die every year. Some of these deaths occur in hospitals and are related to both clinical characteristics and modifiable risk factors. This study investigates the association between malnutrition and mortality and profiles the presenting features in a case-control study of children under 5 years of age who attended Princess Marie Louise Children’s Hospital (PML) in 2011.MethodsA total of 120 cases of children under the age of 5 years who were admitted to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 26 publications
7
23
3
Order By: Relevance
“…On the other hand, other studies showed that more than the half of the deaths had one or multiple problems at the same time implying mainly severe asphyxia at birth, congenital defects, little weight at birth and prematurity [10,13]. Bad nutrition and diarrhea were also comorbidities in Africa [8,24]. This wasn't found in our study.…”
Section: Discussioncontrasting
confidence: 72%
“…On the other hand, other studies showed that more than the half of the deaths had one or multiple problems at the same time implying mainly severe asphyxia at birth, congenital defects, little weight at birth and prematurity [10,13]. Bad nutrition and diarrhea were also comorbidities in Africa [8,24]. This wasn't found in our study.…”
Section: Discussioncontrasting
confidence: 72%
“…The study was part of a bigger child mortality investigation at the hospital which also looked at the causes of death, the main diagnostic categories and the place of residence and mortality [15,16]. We examined clinical characteristics in more detail and risk factors for mortality in a case-control study which compared children who died in 2011 with children who survived in the same year [17]. …”
Section: Methodsmentioning
confidence: 99%
“…Using trend analysis to identify key factors associated with child mortality has become relevant for targeted intervention. The generalisability of some findings from previous studies was limited as most studies in Ghana restricted their analysis to only some selected districts7–9 or a few hospitals 10–12. For studies that pooled data from a different survey, it was not clear how they accounted for sampling weight from different surveys at different time points.…”
Section: Introductionmentioning
confidence: 99%